Genomic organization of the bovine class II MHC studied with field inversion gel electrophoresis - Bensaid, A.M.; Young, J.R.; Kaushal, A.; Teale, A.J. (1988)
In a study Bovine DNA was prepared from a Theileria parva-transformed lymphobastoid cell line derived from the PBM of an heterozygons Boran (Bos indicus) steer. It was observed that linkage between the bovine DR alpha and DR beta subregions on the basis that a 1-2 Mbp Sfi1 and a 0.6 Mbp not 1 fragment hybridized with both probes. In view of the fact that these probes revealed, in addition, urigne extra bands with both enzymes, it is concluded that they may be considered locus-specific in cattle. The DP beta cDNA hybridized with a 0.32 Mbp Sfi1 and 0.6 and 0.1 Mbp Not1 fragments. Only the highest molecular weight fragment seems to be common with the DR region. Sight differences in mobility between the Sfi1 DR beta and DP beta bands (0.3 versus 0.32 Mbp) have been observed. The result suggest that the bovine MHC spans more than 3 MbThe class II region is composed of tightly linked DR alpha and DR beta subregions.